Pregnant women's bonding and maternal-fetal attachment - Schmidt, Eluisa Bordin; Argimon, Irani Iracema de Lima (Paidéia (Ribeirão Preto), 2009)
This study verified the association between the type of pregnant women's bonding, symptoms of anxiety, depression and the level of maternal-fetal attachment. The sample was composed of 136 pregnant women between 18 and 42 years of age, from the sixth to the ninth month of pregnancy, with at least the fifth grade. This is a quantitative, transversal and correlational study. The used instruments were: a social-demographic data form, Adult Bonding Scale (EVA), Maternal-Fetal Attachment Scale (MFAS), the Beck Depression Inventory (BDI), and the Beck Anxiety Inventory (BAI). Data were analyzed through descriptive statistics, Fisher's exact test, Monte Carlo Simulation and Pearson's correlation. Results indicate that there is significant association between the type of pregnant women's bonding, maternal-fetal attachment and depression symptoms. The pregnant women who presented strong bonding showed a high level of maternal-fetal attachment and fewer anxious and depressive symptoms.